Targeting social transfer programmes: Comparing design and implementation errors across alternative mechanisms - Rachel Sabates-Wheeler; Alex Hurrell; Stephen Devereux (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
Identifying the poorest for selection into social transfer programmes is a major challenge facing programme implementers. An innovative cash transfer programme in northern Kenya trialled three targeting mechanisms to learn lessons about which approach is most effective at minimizing inclusion and exclusion errors. We conclude that community-based targeting is the most accurate of the three approaches, followed by categorical targeting by age and household dependency ratio. However, targeting performance is strongly affected by implementation capacity and modalities. Through a simulation exercise we show that a proxy means test would have performed better than single categorical indicators.
Keywords: I38; I32; D60; 330; social transfers; errors; Kenya